Beyond the Genetic Information Nondiscrimination Act: ethical and economic implications of the exclusion of disability, long-term care and life insurance. (March 2017) - Tenenbaum, Jessica D; Goodman, Kenneth W
The Genetic Information Nondiscrimination Act (GINA) was intended to protect individuals in the USA from discrimination based on their genetic data, but does not apply to life, long-term care or disability insurance. Patient advocates and ethicists have argued that GINA does not go far enough. Others express concerns for the viability of insurance companies if millions of potential customers know more than professional actuaries. Here we discuss the exclusion of certain insurance types from GINA. We explore the ethical and economic implications of this distinction, and potential paths forward. We suggest that because long-term care and disability insurance can be essential for well-being, there is no good reason to place them in a class with life insurance and therefore beyond GINA's reach.